Comparative Analysis of Kinetic Models for Simulation of Biogas Production from Cow Dung and Fruit Waste via Anaerobic Digestion - Abdulwadud Yusuf Abdulkarim; Hashim Adamu; Akorode Abdulafeez Olayinka; Oyinkan Ilemore; Kish Elisha Dokas (International Journal of Membranes, 2025)
This study investigates the optimization of biogas and biofertilizer production from cow dung and fruit waste through anaerobic digestion, utilizing various microbial growth kinetic models. Simulations were conducted using the Monod, Moser, Contois, and Tessier models to predict biogas yield and assess model accuracy. Results indicated that the Tessier model provided the closest fit to experimental data, with a biogas yield of 0.45 m³/kg VS, while the Monod model overestimated yields at 0.65 m³/kg VS. The Moser and Contois models produced more realistic estimates of 0.50 m³/kg VS and 0.48 m³/kg VS, respectively. Additionally, the cow dung’s C/N ratio of 30:1, higher than the optimal 20–25:1 range, suggested its greater suitability for biofertilizer production. This study underscores the importance of selecting appropriate kinetic models for accurate simulation and highlights the potential for optimizing feedstock composition to enhance biogas yields, thereby contributing valuable insights into the modeling and optimization of anaerobic digestion processes for sustainable energy production. These findings highlight the critical role of selecting appropriate kinetic models for accurately simulating anaerobic digestion processes and optimizing feedstock composition to enhance biogas yields.
Keywords: anaerobic digestion; biofertilizer; biogas production; cow dung; fruit waste; kinetic models